Connecting, Organizing, Reflecting, Extending Learning Model Assisted By Wordwall Media On Stundents’ Numeracy Skills - Nurjannah Nurjannah; Rohantizani Rohantizani; Nur Elisyah; Muliana Muliana; Haves Qausar; M Mursalin (Electronic Journal of Education, Social Economics and Technology, 2025)
Students’ low numeracy skills are caused by their unfamiliarity in solving word problems, the continued use of conventional learning models, and the limited utilization of instructional media. This research seeks to examine the influence of the Connecting, Organizing, Reflecting, and Extending learning model, supported by Wordwall media, on students' numeracy abilities. This study adopted a quantitative approach through a quasi-experimental design, specifically utilizing the Nonequivalent Control Group framework. The population consisted of all 11 th-grade students at SMAN 1 Kuta Makmur. The sampling technique used was purposive sampling, where class XI A1 was assigned as the experimental group and class XI A2 as the control group. Data collection techniques included observation and testing. The prerequisite tests consisted of the normality test (Shapiro-Wilk), homogeneity test (Levene’s statistic), and Mann-Whitney test, assisted by SPSS 26 software. The hypothesis testing results showed a significance value of 0.002 α (α = 0.05), indicating that the  Connecting, Organizing, Reflecting, Extending  learning model assisted by Wordwall media had a significant effect on students’ numeracy skills. This result demonstrates that students in the experimental class had better numeracy skills than those in the control class.